Environmental Waqf for climate action in the light of Maqasid al-‘Imran: (Hifz al-‘Imran or Hifz al-Bi’ah) - Zakariyah, Habeebullah; Hassan, Rusni; Mohamad Noor, Fatimah (Routledge, 2026)
Environmental degradation has become one of the most pressing global challenges, impacting the entire planet. One of the potential solutions is Waqf, which can contribute significantly to environmental sustainability, including forest restoration and renewable energy development. Hence, this study aims to explore the role of environmental Waqf in addressing climate change, with a focus on the Hifz al-‘Imran (protection of the environment), and to highlight its potential to contribute to effective climate action. The study concludes that Hifz al-‘Imran can provide a strong conceptual foundation for aligning environmental conservation and climate action with the higher objectives of Islamic law.